2023
DOI: 10.1182/bloodadvances.2023009739
|View full text |Cite
|
Sign up to set email alerts
|

Real-world comparative effectiveness of acalabrutinib and ibrutinib in patients with chronic lymphocytic leukemia

Abstract: Novel agents, including Bruton tyrosine kinase inhibitors (BTKis), have become the standard of care for patients with chronic lymphocytic leukemia (CLL). We conducted a real-world retrospective analysis of CLL patients treated with acalabrutinib vs ibrutinib to compare outcomes utilizing the Flatiron Health Database. Patients with CLL were included if they initiated acalabrutinib or ibrutinib between 1/1/2018-2/28/2021. The primary outcome of interest was time to treatment discontinuation (TTD). Average treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…The most common reason for treatment discontinuation was AE/toxicity. This observation is in line with the majority of real-world studies that identified AEs as the main reason for discontinuing ibrutinib [ 18 , 24 , 26 , 27 , 28 , 29 , 41 ] and possibly other BTKi [ 43 ]. Conversely, disease progression was the most frequent cause of treatment discontinuation recorded in RTCs.…”
Section: Discussionsupporting
confidence: 87%
“…The most common reason for treatment discontinuation was AE/toxicity. This observation is in line with the majority of real-world studies that identified AEs as the main reason for discontinuing ibrutinib [ 18 , 24 , 26 , 27 , 28 , 29 , 41 ] and possibly other BTKi [ 43 ]. Conversely, disease progression was the most frequent cause of treatment discontinuation recorded in RTCs.…”
Section: Discussionsupporting
confidence: 87%
“…Our study has strengths such as an expressive sample size and the real-world characteristics of the data. Although other real-word analyses have been conducted between acalabrutinib versus ibrutinib, they focused on the cancer treatment effectiveness such as time to treatment discontinuation (22), differently from us that focused on cardiovascular and non-cardiovascular safety in patients with rstline therapy However, we should recognize several limitations. First, the analysis was retrospective, which can lead to selection bias when analyzing treatment arms.…”
Section: Discussionmentioning
confidence: 94%
“…Acalabrutinib has been approved for CLL therapy and has an efficacy comparable to that of ibrutinib, although with fewer AEs (34). As a result, is was previously demonstrated that patients who received acalabrutinib had a 41% lower risk of discontinuation and a longer time to discontinuation compared to those treated with ibrutinib (35). Acalabrutinib monotherapy given in treatment-naĂŻve patients with CLL was found to be cost-effective compared to chlorambucil + obinutuzumab (36).…”
Section: Covalent Btkismentioning
confidence: 99%